1989
DOI: 10.1128/mcb.9.5.2251
|View full text |Cite
|
Sign up to set email alerts
|

The alternatively spliced exon of the platelet-derived growth factor A chain encodes a nuclear targeting signal.

Abstract: We have previously shown that the SIS/platelet-derived growth factor B chain contains a nuclear targeting signal near its C terminus. Here we show that the platelet-derived growth factor A chain also contains a nuclear targeting signal encoded by an exon which is subject to alternative splicing. This sequence is capable of targeting a nonsecreted form of the A chain to the nucleus and can also target the cytoplasmic proteins dihydrofolate reductase, chloramphenicol acetyltransferase, and pyruvate kinase to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 24 publications
1
39
1
Order By: Relevance
“…Both antibodies exhibit intracellular staining in the myoblasts, whereas the nuclei are conspicuously unstained. These data do not support the hypothesis, proposed by Maher et al (13), that exon 6 encodes a nuclear targeting signal. St.…”
contrasting
confidence: 55%
“…Both antibodies exhibit intracellular staining in the myoblasts, whereas the nuclei are conspicuously unstained. These data do not support the hypothesis, proposed by Maher et al (13), that exon 6 encodes a nuclear targeting signal. St.…”
contrasting
confidence: 55%
“…However, our data permit us to propose a direct role ofIFN--y in the cascade of events involved in signal transduction. Other cytokines, such as platelet-derived growth factor (26) and basic fibroblast growth factor (27), have been shown to contain functional NLSs.…”
Section: Discussionmentioning
confidence: 99%
“…FGF and platelet-derived growth factor have been detected in the nuclei of nonneuronal cells (38)(39)(40)(41)(42), and it recently has been demonstrated that nuclear translocation is essential for maintaining mitogenic activity of acidic FGF (43). While nuclear translocation sequences are not always easily identifiable in protein sequences, they typically consist of 4-10 amino acid residues, rich in the basic amino acids arginine or lysine and often including a proline or a valine (44,45).…”
Section: Discussionmentioning
confidence: 99%